Exercise may cause myocardial ischemia at the anaerobic threshold in cardiac rehabilitation programs - Fuchs,A.R.C.N. (2009)
Myocardial ischemia may occur during an exercise session in cardiac rehabilitation programs. However, it has not been established whether it is elicited when exercise prescription is based on heart rate corresponding to the anaerobic threshold as measured by cardiopulmonary exercise testing. Our objective was to determine the incidence of myocardial ischemia in cardiac rehabilitation programs according to myocardial perfusion SPECT in exercise programs based on the anaerobic threshold. Thirty-nine patients (35 men and 4 women) diagnosed with coronary artery disease by coronary angiography and stress technetium-99m-sestamibi gated SPECT associated with a baseline cardiopulmonary exercise test were assessed. Ages ranged from 45 to 75 years. A second cardiopulmonary exercise test determined training intensity at the anaerobic threshold. Repeat gated-SPECT was obtained after a third cardiopulmonary exercise test at the prescribed workload and heart rate. Myocardial perfusion images were analyzed using a score system of 6.4 at rest, 13.9 at peak stress, and 10.7 during the prescribed exercise (P < 0.05). The presence of myocardial ischemia during exercise was defined as a difference ≥2 between the summed stress score and summed rest score. Accordingly, 25 (64%) patients were classified as ischemic and 14 (36%) as nonischemic. MIBI-SPECT showed myocardial ischemia during exercise within the anaerobic threshold. The 64% prevalence of ischemia observed in the study should not be looked on as representative of the whole population of patients undergoing exercise programs. Changes in patient care and exercise programs were implemented as a result of our finding of ischemia during the prescribed exercise.